Effect of protein-rich diet and the tamarind trypsin inhibitor on behavioral disorders in obese zebrafish - Silva, Ana Karoliny Xavier de Gois; Medeiros, Isaiane; Mamede, João Paulo; Trajano, Aslan Costa; Costa, Thaiz Ivana da Silva; de Sousa, Aline Lopes Marques; de Souza, Larissa Aida Lemos; Nascimento, Amanda Maria de Souza; Silva-Maia, Juliana Kelly da; Morais, Ana Heloneida de Araújo (Frontiers in Nutrition, 2026)
IntroductionObesity is a major public health concern, often accompanied by behavioral and psychological alterations such as anxiety, impaired sociability, and dysregulated stress responses. Nutritional interventions using bioactive compounds from plant sources are emerging as promising strategies to address both metabolic and behavioral aspects of obesity. This study investigated the effects of tamarind trypsin inhibitor (TTI), a plant-derived bioactive protein, on behavioral and stress-related outcomes in diet-induced obese zebrafish (Danio rerio), a recognized translational model for human metabolic and neurobehavioral research.MethodsTTI was isolated and characterized by its molecular mass and enzymatic activity. Zebrafish were fed Artemia sp. at varying quantities, with or without TTI, to assess anxiety-like behavior, social behavior, and their response to acute stress. Obese overfed fish (OH) received 120 mg/fish/day, while eutrophic normofed fish (EN) received 75 mg/fish/day. Obese fish were treated for 10 days with TTI (25 mg/L), either while remaining overfed (OH+TTI) or becoming normofed (ON+TTI). On day 11, behaviors were recorded and analyzed using ANY-maze software.ResultsSignificant differences were found in anxiety-related average speed between OH and OH+TTI (p = 0.01), and between ON and OH+TTI (p = 0.01). Time spent at the top differed between EN and OH+TTI (p = 0.03), and immobility during stress was lower in OH+TTI compared to EN (p = 0.01). In the sociability test, average speed differed between EN and ON+TTI (p = 0.01).DiscussionDespite these findings, no consistent behavioral alterations indicating anxiety, sociability issues, or stress responses were associated with overfeeding or TTI. Thus, TTI did not induce behavioral side effects and may be a promising candidate for obesity treatment, differing from many current pharmacological options. Given the translational relevance of zebrafish to human nutrition and health, these findings highlight the potential of TTI as a candidate bioactive compound for future dietary interventions targeting both metabolic and behavioral outcomes in obesity.